Inhibition of Brd4 by JQ1 Promotes Functional Recovery From Spinal Cord Injury by Activating Autophagy - Li, Yao; Xiang, Jie; Zhang, Jing; Lin, Jiahao; Wu, Yaosen; Wang, Xiangyang (Frontiers in Cellular Neuroscience, 2020)
Abstract Spinal cord injury (SCI) is a destructive neurological disorder that is characterized by impaired sensory and motor function. Inhibition of bromodomain protein 4 (Brd4) has been shown to promote the maintenance of cell homeostasis by activating autophagy. However, the role of Brd4 inhibition in SCI and the underlying mechanisms are poorly understood. Thus, the goal of the present study was to evaluate the effects of sustained Brd4 inhibition using the bromodomain and extraterminal domain (BET) inhibitor JQ1 on the regulation of apoptosis, oxidative stress and autophagy in a mouse model of SCI. First, we observed that Brd4 expression at the lesion sites of mouse spinal cords increased after SCI. Treatment with JQ1 significantly decreased the expression of Brd4 and improved functional recovery for up to 28 day after SCI. In addition, JQ1-mediated inhibition of Brd4 reduced oxidative stress and inhibited the expression of apoptotic proteins to promote neural survival. Our results also revealed that JQ1 treatment activated autophagy and restored autophagic flux, while the positive effects of JQ1 were abrogated by autophagy inhibitor 3-MA intervention, indicating that autophagy plays a crucial role in therapeutic effects Brd4 induced by inhibition of the functional recovery SCI. In the mechanistic analysis, we observed that modulation of the AMPK-mTOR-ULK1 pathway is involved in the activation of autophagy mediated by Brd4 inhibition. Taken together, the results of our investigation provides compelling evidence that Brd4 inhibition by JQ1 promotes functional recovery after SCI and that Brd4 may serve as a potential target for SCI treatment.